ENVIRONMENTAL MANAGEMENT ACCOUNTING PRACTICE IN NIGERIA: NATIONAL PETROLEUM CORPORATION (NNPC) - Abiola, James O.; Ashamu, S. O. (European Scientific Journal, ESJ, 2012)
There is an apparent lack of awareness and understanding of the magnitude of the environmental costs generated by organizations, and many opportunities for cost savings through good environmental management are thus lost. Conversely, conventional management accounting practices do not provide adequate information for environmental management purposes in a world where environmental concern as well as environment-related costs, revenues, and benefits are on the rise. Using a case study of the Nigeria National Petroleum Corporation (NNPC) as an Environmental sensitive sector, this study conducts an assessment of NNPC’s practice of environmental management accounting (EMA) by investigating how the NNPC manages, account for and report its environmental risk performance? The study design will be mainly survey method, using questionnaires to collect data from managers in both the financial and environmental disciplines within the branches and strategic business units of the NNPC with specific case study of Abuja head office and branches in Port Harcourt and Lagos. The result of the study shows that NNPC managers are aware of environmental Accounting practices and that it is actively being used in practice. The findings of the study will further equip NNPC managers and similar policy makers to understand how it accounts for, manages, and reports environmental cost information.